Heavy metal contamination in coastal waters of the southeastern Bay of Bengal: Spatial distribution, potential source patterns, and human health risk assessment - Md. Simul Bhuyan; Vinmoy Mondal; A.J.M. Morshed; Md. Tariqul Islam; Lotfi J. Rabaoui; S. Sekar (Marine Pollution Bulletin, 2026)

Seasonal dynamics of multiple coastal pollutants in the Bhatiari coastal waters, Chattogram, Bangladesh - Md Minarul Hoque; Bipasha Sur; Sultan Al Nahian; Abu Sharif Md. Mahbub-E-kibria; Md. Tarikul Islam; Md. Simul Bhuyan (Regional Studies in Marine Science, 2026)

AI-Driven Geospatial Modeling of Urban Expansion and Environmental Impacts - Frank Juma Ong’ondo; Hafez Ahmad; Felix Jose; Shakila Islam Jhara; Darren J. Shoemaker; Md. Mazaharul Islam; Padmanava Dash; Md. Simul Bhuyan; Md. Nazrul Islam (Remote Sensing in Earth Systems Sciences, 2026)

A review on the effects of iron (Fe) on Ulva prolifera: Mechanisms of growth promotion, inhibition, and biochemical responses - Md Mohidul Islam; Sahr Lamin Sumana; Mukhtar Abdullateef Muhammad; Gelena Urgesa Ayana; Shisi Fu; Abubakar Shuaibu; Ahmed E. Elshafey; Yifei Shen; Yuqing Sun; Md. Simul Bhuyan; Md. Enamul Hoq; Touhidul Hoque Shuvo; et al. (Algal Research, 2026)

Assessment of heavy metals and proximate composition of a jellyfish (Rhizostoma octopus Gmelin, 1791) from Cox's Bazar coast, Bay of Bengal, Bangladesh: Tracing contamination sources and human health risks - Md. Simul Bhuyan; Debasish Pandit; Mohammad Ismail; Mir Mohammad Ali; Md Khalid Saifullah; Md. Tarikul Islam; Ahmed Harun-Al-Rashid; Ummey Hafsa Bithi; Mrityunjoy Kunda; Md. Abu Bakar Siddique (Marine Pollution Bulletin, 2026)

Climate change impacts on coral reefs and emerging resilience pathways: A systematic review - Md. Simul Bhuyan; Maroua Jenzri; Md. Tarikul Islam; Diponkor Adikari; Md Minarul Hoque (Ocean & Coastal Management, 2026)

Heavy metal contamination in sediment of mudskipper habitat along the Cox’s Bazar coast, Bay of Bengal, Bangladesh: Ecological and human health risk assessment using deterministic and probabilistic approaches - Md. Simul Bhuyan; Mohammad Ismail; A.J.M. Morshed; Md. Tariqul Islam; Vinmoy Mondal (Regional Studies in Marine Science, 2026)

Strategies to strengthen institutional capacities for climate-resilient coastal socio-ecological systems in Bangladesh - Ranjan Roy; Liton Chakraborty; Surajit Haldar; Byomkesh Talukder; Mou Leong Tan; Sajib Roy; Md. Simul Bhuyan; Ngai Weng Chan (Climate and Development, 2026)

Impacts of sedimentation on coral health and reef ecosystems: A comprehensive review - Md. Simul Bhuyan; Maroua Jenzri; Diponkor Adikari (Marine Pollution Bulletin, 2025)

Middle Eastern mangroves at the arid limit (Red Sea and Arabian/Persian Gulf): eco-biophysical dynamics, blue-carbon MRV, climate-risk pathways, and governance for resilient restoration - a comprehensive review - Gowhar Meraj; Mohamed Yehia Abouleish; Tarig Ali; Shizuka Hashimoto; Asif Marazi; Rabin Chakrabortty; Suraj Kumar Singh; Shruti Kanga; Mansour Almazroui; Md. Simul Bhuyan (Frontiers in Marine Science, 2025)
Middle Eastern (ME) mangroves, spatially restricted and fragmented at the arid limit of the biome, underpin shoreline protection, fisheries, and blue-carbon initiatives along rapidly urbanizing coasts. However, global generalisations tend to overestimate their functional capacity, risking context mismatched restoration and overestimated offset potential. We conducted a comprehensive multi-method review across the Red Sea, Arabian/Persian Gulf, and adjoining shores. From peer-reviewed and agency sources, the literature was synthesized across four domains: eco-biophysical dynamics, socio-economics, climate-risk pathways, and governance. The review demonstrated that four primary controls govern distribution and function: freshwater inputs, hypersalinity, heat, and sheltering geomorphology. Avicennia marina dominates as dwarf, slow-growing stands of ~2–4 m, allocating resources below ground on carbonate and nutrient-poor substrates. Vertical accretion is modest ~1–3 mm yr - ¹, organic carbon burial is low ~10–15 g C m - ² yr - ¹, and soil stocks are small ~43 ± 5 Mg C ha - ¹ relative to the humid tropics. A wave-energy threshold and micro- to mesotidal ranges constrain the flushing. Sea-level rise (SLR) of 2.92 mm yr - ¹, with a projected increase of 39.1 cm by 2100, combined with thermal and salinity extremes, dust burial, and oiling, raises the risk. However, undisturbed soils confer high carbon permanence. Socio-economic benefits, such as nursery support, shoreline defense, and cultural amenities, are large, but enforcement, monitoring, reporting, and verification (MRV), and co-management remain uneven. A region-specific framework is most essential. Priorities are to safeguard groundwater-fed refugia, secure retreat corridors, reduce local stressors, and implement stress-matched restoration that replicates resilient features, such as space, sediment, seepage, and shelter, while grounding mitigation in arid-zone MRV and avoided-loss accounting. This study provides a resilience–threat typology and integrated governance framework linking legal protection, climate-linked restoration, regional coordination, and inclusive co-management.

Microplastics occurrence in sea cucumbers and impacts on sea cucumbers & human health: A systematic review - Md. Simul Bhuyan; Maroua Jenzri; Debasish Pandit; Diponkor Adikari; Md. Wahidul Alam; Mrityunjoy Kunda (Science of The Total Environment, 2024)

Assessment of heavy metals and proximate composition in jellyfish (Lobonemoides robustus Stiasny, 1920) collected from Cox's Bazar coast: Human health risk assessment - Md. Simul Bhuyan; Md. Tarikul Islam; Sayeed Mahmood Belal Haider; Lamia Yacoubi; Mala Khan; Mir Mohammad Ali; Debasish Pandit; Md. Mainul Huda; Sheuly Akter; Md. Raisul Islam Rabbi; Nayan Kumer Kundu; Md. Mehedi Hasan; et al. (Marine Pollution Bulletin, 2024)

A comprehensive scenario of heavy metals pollution in the rivers of Bangladesh during the last two decades - Debasish Pandit; Mohammad Mahfujul Haque; Md. Simul Bhuyan; Ahmed Harun-Al-Rashid; Partho Protim Barman; Rana Roy; Bishwajit Sarker; Md. Khalid Saifullah; Mrityunjoy Kunda (Environmental Science and Pollution Research, 2024)

Seasonal influence of freshwater discharge on spatio-temporal variations in primary productivity, sea surface temperature, and euphotic zone depth in the northern Bay of Bengal - Hafez Ahmad; Felix Jose; Md. Simul Bhuyan; Md. Nazrul Islam; Padmanava Dash (Acta Oceanologica Sinica, 2024)

Trace element levels in the muscles of three tern species (Aves: Laridae) from the western Arabian Gulf: environmental assessment and implications for conservation - Lamia Yacoubi; Dario Savoca; Radhouan Belgacem El Zrelli; Jinoy Gopalan; Mazen Nazal; Yu-Jia Lin; Antonella Maccotta; Foued Hamza; Md. Simul Bhuyan; Marco Arculeo; Lotfi Jilani Rabaoui (Environmental Monitoring and Assessment, 2024)
In the Arabian Gulf (called also Persian Gulf; hereafter 'the Gulf'), Jana and Karan Islands are recognized as one of the most Important Bird Areas in the region. Many migratory breeding seabirds, like the Greater Crested Tern Thalasseus bergii , White-cheeked Tern Sterna repressa and Bridled Tern Onychoprion anaethetus , depend on these islands during the breeding season. However, these aquatic wildlife species are suffering from intensified urban and industrial coastal development and various contamination events including wars and related oil spills. In this study, we used these three piscivorous top predator birds to analyse the levels of 19 trace elements (TEs; i.e. Al, As, Ba, Ca, Cd, Co, Cr, Cu, Fe, Hg, K, Mg, Mn, Na, Ni, Pb, Sr, V and Zn) in 15 muscular tissue samples from Jana and Karan Islands. PERMANOVA analysis showed no difference in contamination profile between sites nor between species probably due to their spatial and ecological proximity and therefore similar levels of exposure to TEs. Comparing these levels with existing literature, our results showed no particular concern for all elements, except for Al (maximum values recorded = 116.5 µg g −1 d.w.) and, in two samples, Ba (33.67 µg g −1 d.w.) and Pb (5.6 µg g −1 d.w.). The results can be considered as an initial step for supplementary evaluations with a larger number of samples and specified time intervals for the collection of specimens. This study provided baseline information on the pollution status of these two ecologically important sites which require a continuous biomonitoring programme.

A review on sea cucumber (Bengali: Somuddro Sosha) as a bioindicator of heavy metal contamination and toxicity - Md. Simul Bhuyan; Levent Bat; Venkatramanan Senapathi; Prabakaran Kulandaisamy; Selvam Sekar; Sayeed Mahmood Belal Haider; Gowhar Meraj; Md. Tarikul Islam; Mrityunjoy Kunda; Md. Wahidul Alam; Lotfi Rabaoui (Marine Pollution Bulletin, 2024)

Determining synergies and trade-offs between adaptation, mitigation and development in coastal socio-ecological systems in Bangladesh - Ranjan Roy; Moynul Hasan Monju; Mou Leong Tan; Md. Sadique Rahman; Shilpi Kundu; Md. Shahinoor Rahman; Byomkesh Talukder; Md. Simul Bhuyan (Environmental Development, 2023)

Correction to: Heavy metal (As, Cr, and Pb) contamination and associated human health risks in two commercial fish species in Bangladesh - Maria Al Mazed; Md Ayenuddin Haque; Md Mehedi Iqbal; Saifuddin Rana; Kabir Ahammad; Md Fahad Bin Quader; Sk Ahmad Al Nahid; Md Simul Bhuyan; Venkatramanan Senapathi; Md Masum Billah; Sk Istiaque Ahmed (Environmental Monitoring and Assessment, 2023)

Bioaccumulation of trace elements and hydrocarbons in chondrichthyans of the western Arabian Gulf: Environmental and human health risk assessment and implications for conservation - Lamia Yacoubi; Radhouan Belgacem El Zrelli; Hua Hsun Hsu; Yu-Jia Lin; Dario Savoca; Jinoy Gopalan; Mazen Nazal; Md. Simul Bhuyan; Marco Arculeo; Lotfi Jilani Rabaoui (Science of The Total Environment, 2023)

Novel machine learning algorithms to predict the groundwater vulnerability index to nitrate pollution at two levels of modeling - Hussam Eldin Elzain; Sang Yong Chung; Senapathi Venkatramanan; Sekar Selvam; Hamdi Abdurhman Ahemd; Young Kyo Seo; Md. Simul Bhuyan; Mohamed A. Yassin (Chemosphere, 2023)

Inferences on metal pollution in the natural spawning zone of Bangladesh river and pollution management strategies - Md. Wahidul Alam; Mohammad Mostafizur Rahman; Md. Simul Bhuyan; Venkatramanan Senapathi; Sang Yong Chung; Sivakumar Karthikeyan; Selvam Sekar; Hussam Eldin Elzain; Ata Allah Nadiri (Environmental Monitoring and Assessment, 2023)

Ecological risks associated with seaweed cultivation and identifying risk minimization approaches - Md. Simul Bhuyan (Algal Research, 2023)

Trace Element Risk Assessment for the Consumption of Sarda sarda (Bloch, 1793) from the mid-South Black Sea Coastline - Levent Bat; Ayşah Öztekin; Elif Arici; Fatih Şahin; Md. Simul Bhuyan (Water, Air, & Soil Pollution, 2022)

Metals in Wild and Cultured Dicentrarchus labrax (Linnaeus, 1758) from Fish Markets in Sinop: Consumer’s Health Risk Assessment - Levent Bat; Fatih Şahin; Md. Simul Bhuyan; Elif Arici; Ayşah Öztekin (Biological Trace Element Research, 2022)

Spatiotemporal variation and toxicity of trace metals in commercially important fish of the tidal Pasur River in Bangladesh - Mir Mohammad Ali; Mohammad Lokman Ali; Md. Simul Bhuyan; Md. Saiful Islam; Md. Zillur Rahman; Md. Wahidul Alam; Monika Das; Sobnom Mustary; Md. Nazrul Islam (Environmental Science and Pollution Research, 2022)

Seasonal variation of heavy metals in water and sediments in the Halda River, Chittagong, Bangladesh - Md. Simul Bhuyan; Muhammad Abu Bakar (Environmental Science and Pollution Research, 2017)